Environmental security and ecoterrorism - Alpas, Hami; Berkowicz, Simon M.; Ermakova, Irina (NATO science for peace and security series C: environmental security, 2011)
In recent years, the concept of environmental security has been adapted to include preparedness for acts of ecoterrorism. This latter term has now become synonymous with environmental terrorism where the perpetrator uses the environment as a weapon to harm an opponent. The intended outcome is usually large-scale deaths, severe damage to the environment, and instilling fear in the general population. This book explores various facets of ecoterrorism including the role of the state in pursuing and maintaining environmental security, a review of the concept of ecoterrorism, food security challenges and weaknesses, technological countermeasures to enable rapid detection or response, and existing pollution sources and hazards that may serve as targets for terrorist acts. In sum, this volume provides a useful overview for both the layperson and experienced researchers.